Pengabaian Nafkah Anak Secara Sengaja oleh Ayah Pasca Perceraian - Andriyani, Andriyani; Qodariah Barkah; Ifrohati, Ifrohati (Universitas Internasional Batam, 2025)
This study examines the legal issue of fathers deliberately neglecting child support obligations following divorce, despite existing court rulings mandating such support. The research aims to analyze the criminal liability of fathers who intentionally disregard post-divorce child support obligations and to assess this issue within the context of national and Islamic law. This study employs a normative juridical method with a descriptive qualitative approach. The findings reveal that fathers who intentionally fail to provide child support after divorce can be classified as committing child neglect, which constitutes a criminal offense under Indonesian law, specifically the Child Protection Law No. 35 of 2014 and the Criminal Code, with potential penalties of up to five years' imprisonment or fines. From the perspective of Islamic law, a father’s obligation to support his child remains intact regardless of marital status, as stipulated in the Qur'an and the Compilation of Islamic Law. This research highlights that protecting children’s rights is a fundamental responsibility of the state, family, and society, which must be enforced firmly through civil and criminal measures to create a deterrent effect for fathers who neglect their obligations. Consistent and integrated legal enforcement is essential to ensure that children receive their rightful support, enabling them to grow and develop properly while preventing psychological and social harm resulting from the father's deliberate neglect after divorce. These findings call upon legal practitioners, policymakers, and community leaders to strengthen enforcement frameworks, foster legal awareness among fathers, and uphold children’s welfare as a priority within post-divorce family structures.